(untitled) (NeoEcon review, 2026)
Following the 2020 conflict, large-scale reconstruction and resettlement initiatives in Karabakh and East Zangezur have made labor market reintegration a central condition for sustainable economic stabilization. This article examines the mismatch between the employment potential of returning populations and the emerging regional economic structure, assessing its implications for long-term development. The analytical framework is grounded in Human Capital Theory, institutional economics and post-conflict recovery models. Methodologically, the study relies on the analysis of official statistical data and the evaluation of state employment and reconstruction programs. The findings indicate that infrastructure-led investments predominantly generate temporary employment, while the transition toward sustainable and productivity-enhancing jobs in manufacturing and services remains constrained by structural and institutional barriers. The discrepancy between the skill composition of the returning workforce and regional economic priorities weakens the labor market’s capacity to integrate labor supply effectively. The article proposes a strategic approach to human capital recovery within the frameworks of green economy and smart village development, emphasizing the necessity of coordinated institutional reforms to ensure durable socio-economic reintegration.